Determinants of unemployment in Sabah Long-Run and Short-Run analysis - Marcilla Elmy Girl Malasius; James Alin; Mori Kogid; Jaratin Lily (Penerbit Universiti Malaysia Sabah, 2025)
This study explores the determinants of unemployment in Sabah from 1982 to 2020. This study utilized the Autoregressive Distributed Lag order (ARDL) model to investigate the linear relationship between job vacancies, economic growth, government spending, labor force participation, and inflation on unemployment. Job vacancies were disaggregated into five types based on occupations to better understand the symmetric relationship between unemployment and vacancies based on the Beveridge curve theory. Alongside Beveridge Curve theory, this study included Okun’s Law, Keynesian theory of fiscal policy, and Phillips curve theory, which explain the factors of unemployment. Findings revealed that unemployment was influenced by economic growth (GDP) and inflation (CPI) in Sabah.